A multi-stratal perspective on circumstantial meaning. (4th May 2020) - Dreyfus, Shoshana; Hao, Jing
ABSTRACT: This paper provides a "broader" understanding of what is previously known from a grammatical perspective as "circumstantial meaning" or circumstantiation. This "broader" perspective takes into account more abstract meanings beyond grammar, considering both field (at the register stratum) and discourse semantics, in addition to lexicogrammar. The paper shows how the lexicogrammar alone is not able to adequately account for the meaning potential of "circumstantial meaning", and how by examining this region of meaning from three strata, a fuller account of circumstantial meaning is made possible. A richer account of circumstantial meaning is necessary because, while circumstances may be considered structurally peripheral, earlier explorations of circumstantial meaning show that this area of meaning often makes important contributions to the register of any given text and to the building of disciplinary knowledge. This exploration is demonstrated through two texts: a student's high scoring piece of creative writing from the subject of English in the final year of schooling and a synopsis of a history book on the Chinese fishing industry in colonial Australia. These texts reveal the significantly different ways in which circumstantial meanings are used in different subject areas – i.e., to contribute to setting up an "ambience" in literary texts and to developing knowledge in history.